A green MnMgZn phosphate coating for steel pipelines transporting CO2 rich fluids - Magdi Morks; Penny Corrigan; Nick Birbilis; Ivan Cole (2012)
The transport of CO2 rich fluids via steel pipelines in the CO2 capture and storage (CCS) process requires a strategy for internal corrosion protection in cases where the stream is acidic and hence corrosive due to the formation of carbonic acid. Such protection strategies have been scarcely studied and will need significant research. In this study, one possibility to protect the steel pipelines from internal corrosion during CO2 transport is presented based on treatment of the internal surface with a vanadate-based MnMgZn phosphate coating. The addition of sodium orthovanadate (Na3VO4) in a MnMgZn phosphate bath leads to a significant change in the microstructure of the phosphate coating, which will alter corrosion behaviour significantly. Herein, the effect of vanadate concentration (0.0625, 0.125, 0.25 mM) in the phosphate bath is studied with respect to the resultant microstructure and corrosion behaviour of the phosphate coatings. Electrochemical studies such as polarization curves and electrochemical impedance spectroscopy (EIS) were performed in diluted HCl solution at pHs 2-4 to investigate the corrosion behaviour and distinguish the dielectric and electric properties of the phosphate coating.